Eksplorasi Diglosia Dalam Masyarakat Berbahasa Jawa: Pendekatan Sosiolinguistik Dan Kajian Literatur - Salwa Sania Adawiah; Seni Melani; Ichsan Fauzi Rachman (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The use of Javanese in society is an important challenge in an increasingly connected era of globalization. The phenomenon of diglossia, where two or more language variants are used in one language community, is important to research. This research aims to explore the dynamics of diglossia in Javanese-speaking communities using a sociolinguistic approach and literary studies. The literature study method is used to collect data from various relevant literary sources, including books, literature, notes and other sources. The data analyzed includes findings about the use of Javanese in various life contexts, factors that influence diglossia, and the social and cultural impact of changes in language use patterns. The research results show that social and technological changes have brought about a shift in the use of Javanese, with the younger generation tending to switch to Indonesian or foreign languages ​​in daily communication. Factors such as education level, age, social stratification, and family attitudes influence language use preferences in society. In facing these changes, efforts to develop the Javanese language are very important to maintain local language and culture in this era of globalization.